2010
DOI: 10.1161/circulationaha.109.926873
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and Causes of Death in Patients With Severe Symptomatic Aortic Stenosis Who Are Not Eligible to Participate in a Clinical Trial of Transcatheter Aortic Valve Implantation

Abstract: Background— Transcatheter aortic valve implantation is currently being evaluated in patients with severe aortic stenosis who are considered high-risk surgical candidates. This study aimed to detect incidences, causes, and correlates of mortality in patients ineligible to participate in transcatheter aortic valve implantation studies. Methods and Results— From April 2007 to July 2009, a cohort of 362 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 21 publications
1
54
0
Order By: Relevance
“…1,2) After the onset of symptoms, patients with severe AS have a poor prognosis with a one-year mortality of 30%-50% with conservative therapy. 3,4) Given current population projections, it is reasonable to expect that the number of patients affected by aortic valve disease will also increase in the coming years.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) After the onset of symptoms, patients with severe AS have a poor prognosis with a one-year mortality of 30%-50% with conservative therapy. 3,4) Given current population projections, it is reasonable to expect that the number of patients affected by aortic valve disease will also increase in the coming years.…”
Section: Introductionmentioning
confidence: 99%
“…16 Several studies have correlated the presence of renal insufficiency before the procedure with increased mortality. 9,17,18 A study of 262 patients at high surgical risk undergoing BAV showed that creatinine clearance ≤ 60 mL/min before the procedure is a strong predictor of mortality. 7 The absence of vascular complications in this study may be related to the use of sheaths with small calibre (10F) in all patients, as well as to the immediate withdrawal of the sheath.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical repair is the only effective treatment for symptomatic aortic stenosis; however, some patients may not be considered surgical candidates or may require medical stabilization before surgery; other patients refuse surgical options altogether. 6,25 For patients who do not have surgical repair, medical management of angina, exertional syncope, and signs and symptoms of heart failure becomes necessary.…”
Section: Medical Management Of Symptomatic Patientsmentioning
confidence: 99%
“…In another study 6 of 274 medically managed patients with severe aortic stenosis, 66.4% of whom had concomitant coronary artery disease, the cardiac related mortality rate in the median follow-up period of 377.5 days was 43.1%, including a sudden cardiac death rate of 3.9%.…”
mentioning
confidence: 96%